Mendidik Si Kecil dan Teologi: Analisis Filsafat Pendidikan Klasik Perennialisme, Esensialisme dan Rekonstruksionisme - Jabes Pasaribu; Ervi Johan Lo; Tiurma Basa Marina Simanjuntak (Institut Kristen Teologi REAL Batam, 2026)
Early childhood education is frequently approached through a technical-pedagogical lens without adequate philosophical foundations, while classical educational philosophy continues to operate in relative isolation from Christian educational theology. This gap constitutes the departure point of this study. This research aims to construct an integrative conceptual framework connecting three streams of classical educational philosophy (Perennialism, Essentialism, and Reconstructionism) with Christian educational theology for early childhood, employing “the Little One” as an anthropological metaphor denoting the human person in a state of becoming as a subject of Imago Dei. The method employed is a critical-philosophical literature study with an interdisciplinary approach between educational philosophy and Christian theology, conducted through systematic stages of literature exploration, conceptual categorization, critical-comparative analysis, and theological synthesis. The findings reveal that Perennialism contributes to the transmission of enduring values sourced from God as the origin of universal truth, yet requires pedagogical reinterpretation to remain responsive to the holistic development of young children; Essentialism provides a foundation for structured and systematic character formation consonant with the Biblical mandate, though it must be guarded against passive transmission tendencies that undermine children's agency; while Reconstructionism opens the transformative dimension of Christian education through forming children as Gospel-grounded agents of change, albeit with its transformative vision needing to be corrected by divine revelation rather than human critical reason alone. The integration of all three produces a holistic transmit–form–transform paradigm for Christian early childhood education. This study contributes to the development of philosophically grounded Christian educational theology and carries practical implications for churches, families, and educational institutions in nurturing a new generation intellectually, spiritually, and socially in the light of Christ. Keywords: early childhood; classical educational philosophy; perennialism and essentialism; reconstructionism; Christian educational theology and Imago Dei Abstrak Pendidikan anak usia dini sering kali didekati secara teknis-pedagogis tanpa fondasi filsafat yang memadai, sementara diskursus filsafat pendidikan klasik masih berjalan terpisah dari kerangka teologi pendidikan Kristen. Kesenjangan inilah yang menjadi titik berangkat penelitian ini. Penelitian ini bertujuan membangun kerangka konseptual integratif antara tiga aliran filsafat pendidikan klasik (Perennialisme, Esensialisme, dan Rekonstruksionisme) dengan teologi pendidikan Kristen bagi anak usia dini, dengan ”Si Kecil” sebagai metafora antropologis yang menunjuk pada manusia dalam kondisi becoming sebagai subjek Imago Dei. Metode yang digunakan adalah studi literatur kritis-filosofis dengan pendekatan interdisipliner antara filsafat pendidikan dan teologi Kristen, melalui tahapan eksplorasi literatur, kategorisasi konsep, analisis kritis-komparatif, dan sintesis teologis. Hasil kajian menunjukkan bahwa Perennialisme berkontribusi pada pewarisan nilai-nilai abadi yang bersumber dari Allah sebagai Sumber kebenaran universal, namun memerlukan reinterpretasi pedagogis agar responsif terhadap perkembangan holistik anak usia dini; Esensialisme memberikan landasan bagi pembentukan karakter yang terstruktur dan sistematis yang sejalan dengan mandat Alkitab, namun harus dihindari dari kecenderungan transmisi pasif yang mengabaikan agensi anak; sedangkan Rekonstruksionisme membuka dimensi transformatif pendidikan Kristen melalui pembentukan anak sebagai agen perubahan yang berpijak pada Injil, meski visi transformasinya harus dikoreksi oleh penyataan ilahi, bukan semata rasio kritis manusiawi. Integrasi ketiganya menghasilkan paradigma mewariskan–membentuk–mentransformasi yang holistik bagi PAUD Kristen. Penelitian ini berkontribusi pada pengembangan teologi pendidikan Kristen yang berbasis filsafat sekaligus memberikan implikasi praktis bagi gereja, keluarga, dan lembaga pendidikan dalam mendidik generasi baru secara intelektual, spiritual, dan sosial dalam terang Kristus. Kata Kunci: anak usia dini; filsafat pendidikan klasik; perennialisme dan esensialisme; rekonstruksionisme; teologi pendidikan Kristen dan Imago Dei